In vivo anti-lymphoma activity of an agonistic human recombinant anti-TRAIL-R2 minibody. - Zauli, Giorgio; Corallini, Federica; Zorzet, Sonia; Grill, Vittorio; Marzari, Roberto; Secchiero, Paola (Invest New Drugs, 2012)
A new single-chain fragment variable (scFv) to TRAIL-R2 receptor produced as minibody (MB2.23) was characterized for anti-lymphoma activity in vivo. For this purpose, a disseminated lymphoma model was generated by intraperitoneal inoculation of BJAB cells in severe combined immunodeficiency mice. Two weekly injections with MB2.23 (10 mg/kg) were able to significantly increase the median survival time of lymphoma-bearing animals with respect to the vehicle-treated control mice, providing a rationale for further investigating the use of MB2.23 in anticancer therapy.
Keywords: Animals; Humans; Immunotherapy; Injections, Intraperitoneal; Lymphoma, B-Cell; Mice; Mice, SCID; Receptors, TNF-Related Apoptosis-Inducing Ligand; Single-Chain Antibodies; Time Factors; Xenograft Model Antitumor Assays